2014
DOI: 10.1186/2050-6511-15-63
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of treatments for idiopathic pulmonary fibrosis: systematic review, network meta-analysis and health economic evaluation

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a life-limiting lung disease with considerable impact on patients and carers as the disease progresses. Currently few treatments are available. We aimed to evaluate the clinical and cost-effectiveness of available treatments for IPF.MethodsSystematic reviews of clinical effectiveness, quality of life and cost effectiveness were undertaken. Eleven bibliographic databases were searched from inception to July 2013 and studies were assessed for eligibility against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
2
27
0
2
Order By: Relevance
“…An important area for future research is the effect of PR on healthcare costs. Although the clinical effectiveness of PR in ILD is increasingly understood, clarification of cost effectiveness of PR would provide impetus for commissioners and policy makers to ensure this intervention is widely available [Loveman et al 2014]. The NICE clinical guideline of IPF has begun this process by modelling the cost effectiveness of PR, suggesting that it could be cost effective to deliver this intervention every 6-12 months, which could make it possible for PR to be a standard treatment in IPF [NICE, 2013].…”
Section: Possible Future Directionsmentioning
confidence: 99%
“…An important area for future research is the effect of PR on healthcare costs. Although the clinical effectiveness of PR in ILD is increasingly understood, clarification of cost effectiveness of PR would provide impetus for commissioners and policy makers to ensure this intervention is widely available [Loveman et al 2014]. The NICE clinical guideline of IPF has begun this process by modelling the cost effectiveness of PR, suggesting that it could be cost effective to deliver this intervention every 6-12 months, which could make it possible for PR to be a standard treatment in IPF [NICE, 2013].…”
Section: Possible Future Directionsmentioning
confidence: 99%
“…Tolerance data were also evaluated in the meta-analysis of IPF and hypersensitivity pneumonitis patients by JIANG et al [17], demonstrating increased risks of mild gastrointestinal, dermatological and neurological complaints. A subsequent network meta-analysis, looking at the effectiveness of various treatments for IPF, including pirfenidone and nintedanib, showed that only these two therapies were of significant benefit [18]. The limitations of this form of analysis were the indirect comparison of treatments not formally assessed in head-to-head trials and the combination of different end-points to gauge efficacy.…”
mentioning
confidence: 99%
“…Third, among the other unknowns are the utility of either drug in patients with advanced IPF and/or advanced age with varied comorbidities. Fourth, there are concerns that the drugs may not be cost-effective, at least in the prevalent health-care delivery systems in some countries [37]. Lastly, these drugs will alter the design of future studies of newer drugs with the requirement for a new standard-of-care (control) arm in randomized clinical trials.…”
Section: Review Of Current Drugsmentioning
confidence: 99%